Purine analogs as phosphatidylinositol 4-kinase IIIβ inhibitors. Issue 11 (1st June 2016) - Šála, Michal; Kögler, Martin; Plačková, Pavla; Mejdrová, Ivana; Hřebabecký, Hubert; Procházková, Eliška; Strunin, Dmytro; Lee, Gary; Birkus, Gabriel; Weber, Jan; Mertlíková-Kaiserová, Helena; Nencka, Radim
Graphical abstract: Abstract: We report on an extensive structure–activity relationship study of novel PI4K IIIβ inhibitors. The purine derivative of the potent screening hit T-00127-HEV1 has served as a suitable starting point for a thorough investigation of positions 8 and 2. While position 8 of the purine scaffold can only bear a small substituent to maintain the inhibitory activity, position 2 is opened for extensive modification and can accommodate even substituted phenyl rings without the loss of PI4K IIIβ inhibitory activity. These empirical observations nicely correlate with the results of our docking study, which suggests that position 2 directs towards solution and can provide the necessary space for the interaction with remote residues of the enzyme, whereas the cavity around position 8 is strictly limited. The obtained compounds have also been subjected to antiviral screening against a panel of (+)ssRNA viruses.